COVID 19 Outbreak and Tokyo 2020 Olympic Games: A Perspective from Japan’s Economy and Capital Market (Journal of Entrepreneurship and Business, 2022)
This study highlights the key impacts of hosting an international sports event, Tokyo 2020 Olympic Games, during the period of deadliest contagious disease outbreak in history, COVID 19.  The perspective is analysed in terms of the performance of capital market, investment market and sectoral market by the indexes of TOPIX, Stock Market, Bond Market, Foreign Exchange, FTSE, MSCI, and sectoral index of Air Transportation, Construction, Pharmaceutical which shows different range of fluctuation.
Keywords: Array; Array; Array; Array